PENGARUH ASIMETRI INFORMASI, MANAJEMEN LABA, DAN PENGUNGKAPAN MODAL INTELEKTUAL TERHADAP BIAYA MODAL EKUITAS - Togi Antonius Panjaitan; Sofian Sofian (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2022)
This research was conducted with the purpose of knowing the effect of information asymmetry, earnings management and intellectual capital disclosure on the cost of equity capital. The data used in this study is secondary data with the object of research being all companies that are members of the LQ45 index, where the data is obtained from financial reports and the official website of the Indonesian Stock Exchange. The method used in this research is purposive sampling method on certain criteria and the data analysis used is multiple linear regression analysis. The results of this study indicate that earnings management has a positive effect on the cost of equity capital, while information asymmetry and disclosure of intellectual capital have no effect on the cost of equity capital.